Inhibition of Growth and Migration of Esophageal Squamous Cell Carcinoma Cells by Orange Peel Extract and Naringin - mahboubeh tajaldini; Firooz Samadi; Ayyoob Khosravi; Azim Ghasemnejad; Jahanbakhsh Asadi (Medical Laboratory Journal, 2020)
ABSTRACT Background and Objectives: Citrus fruits and their constituents especially naringin (NR), a natural predominant flavanone, have a wide range of pharmacological activities without toxicity against cancer cells. The aim of this study was to investigate the anticancer effects of orange peel extract (OPE) and naringin (NR) on esophageal squamous cell carcinoma (ESCC) cells. Methods: Amount of phenol, flavonoid and antioxidants in OPE was determined using Folin-Ciocalteu procedure, aluminum chloride colorimetric and DPPH assays, respectively. Effects of NR and OPE on viability, wound healing assay and DNA fragmentation using DAPI were investigated. Data were analyzed by ImageJ software and GraphPad Prism 6.0 at significance of 0.05. Results: Total amount of phenols, flavonoids and 1,1-diphenyl-2-picrylhydrazyl was 2.83, 2.143 and 60.76 g/100g of OPE. Amount of NR in the dried OPE was estimated to be 5.260 (µg/gr) using high-performance liquid chromatography. Treatment of ESCC cells with OPE or NR decreased viability y of cancer cells in a dose-dependent manner. In addition, both OPE and NR were able to decrease cell migration and increase DNA fragmentation. Conclusion: The findings of our study suggest that OPE and NR have anticancer effects on ESCC cells but the anticancer effects of OPE was better than that of NR alone. Keywords: Orange peel extract, Naringin, Migration, Esophageal squamous cell carcinoma.